Endophthalmitis in HIV Infection. (2nd October 2020) - Tsirouki, Theodora; Steffen, Jonel; Dastiridou, Anna; Praidou, Anna; Androudi, Sofia
ABSTRACT: Purpose : The role of HIV infection in exogenous and endogenous endophthalmitis has not been clarified. We aim to assess the potential role of HIV as a risk factor or a poor prognostic feature in this sight-threatening condition. Methods : Literature review. Review of evidence : Evidence for endophthalmitis in HIV patients is based on scarce retrospective case series and case reports. Infrequency of literature on this topic is owed to the diversity of the different types of endophthalmitis as well as the rarity of the coexistence of the two conditions. Conclusions : Endophthalmitis in HIV patients are a rare but potentially devastating condition. Many forms of endophthalmitis tend to occur in severely immunosuppressed HIV patients with low CD4 counts. Therefore, the early introduction of cART with full immune reconstitution is an essential part of the prevention of endophthalmitis in the HIV population.